Introduction of fibrin adhesive system (tissucol) in periodontal surgery part I: Suture substitution and wound healing (Mustansiria Dental Journal, 2004)
The present investigation was undertaken ot study the efficacy of fibrin adhesive system (tissucol) sa a substituting material ot hte traditional suturing, and ot compare the clinical findings obtained ni case of traditional suture, thus, two groups each of 12 adult periodontitis patients of nearly equal age, were subjected ot the repositioned flap, apicaly repositioned flap, modified Widmann flap and free gingival graft surgical procedures. Haemostatic time (H.T.), flap adaptation time (F.A.T.), postoperative discomfort time (P.O.D.T.) (pain and swelling) and clinical healing achievement time C.H.A.T. of tissucol group (T.G.) were compared ot those of suturing group (S.G.). This study showed that fibrin adhesive system provides rapid haemostatic action and excellent fap adaptation. Its introduction shortened significantly the clinical healing period of wounded area and shortened the postoperative tim